Difusão de acervos fotográficos: o patrimônio documental de instituições de Santa Maria - RS - Camargo, Eliete Regina Rabaioli (2017)
Photographs are documentary sources that help keep alive the history and memory of a group of people or of society, as well as allowing in-depth analysis, rich in detail and information. In this context, the objective of the research is to disseminate the photographic collections of public and private institutions of Santa Maria to researchers and the community in general, through the elaboration of a guide of sources, with relevant information of the institutions and the collections so that new researchers know about the information potential preserved in different collections of the city. Scientific research consists of a qualitative, exploratory and descriptive approach. The methodological procedures were approached following the objectives and divided into:1) Survey of researched institutions in the Course Completion work: in the undergraduate program in Archivology and Post - graduation in Distance Learning in Archives Management and in the Professional Master 's Degree in Cultural Heritage, all linked to the Federal University of Santa Maria, with photography Between the years 2005 to 2014; 2) Data collection with application of the questionnaire to the responsible ones and survey of the information of the institutions and the photographic collections; 3) Definition of three representative photographs to be displayed on the product; 4) Elaboration of the guide of sources and dissemination in the electronic pages of each institution and in the Municipal Historical Archive of Santa Maria so that there is more comprehensiveness. Of the 16 institutions covered in the course conclusion work, 12 collaborated with the research, three of the institutions claimed problems in the collection and one of them did not return to the contacts made. It was verified, from the study, that the institutions of Santa Maria, from several areas of activity, contain a photographic collection of relevance for the research. In addition to the history of the institution, they have information related to the city, because they are institutions with years of service and for reference in the services they provide. It is hoped that the product will be divulged, reaching the reach of several social classes and groups, that the users enjoy this work directing and facilitating the information that they need for the research, thus conducting new studies. It is also intended that the Font Guide be updated as new information is inserted into the files. It is believed that this work, besides the recognition of the information of the collection, will contribute to the valorization and dissemination of the activities of each institution and that they preserve the sources of the collections that they contain.